Anammox reactor optimization for the treatment of ammonium rich digestate lagoon supernatant - Step feeding mitigates nitrite inhibition. (September 2019) - Yang, Sen; Xu, Shengnan; Mohammed, Abdul; Guo, Bing; Vincent, Simon; Ashbolt, Nicholas J.; Liu, Yang
Abstract: A laboratory-scale anammox integrated fixed-biofilm activated sludge sequencing batch reactor (IFAS-SBR) was operated for 339 days as the post treatment of a nitritation reactor treating ammonium rich digestate lagoon supernatant. By shortening the hydraulic retention time (HRT) from 2.5 d to 1.7 d, the inorganic nitrogen (N) loading rate increased from 0.38 ± 0.00 kg m 3 d −1 to 0.61 ± 0.02 kg m −3 d −1 ; this led to a slight enhancement in the anammox activity. While the activity of anammox bacteria was inhibited by the interim accumulation of NO2 − -N (141.2 – 219.2 mg L −1 ) in the reactor when the HRT was further reduced to 1.2 d, changing the reactor feeding strategy mitigated the nitrite inhibition and restored anammox activity. The presence of organic carbon in lagoon supernatant facilitated the growth of heterotrophic denitrifiers in the reactor; however, this had little impact on N reduction (93.2 ± 3.8% by anammox). Additional batch experiments and sequencing batch reactor cycle tests compared anammox bacterial specific activities under different operating strategies. The dynamics of anammox bacteria and heterotrophic denitrifiers along with the operating strategy changes were documented by qPCR analyses. Our study underlines the importance of optimizing operating strategies within anammox reactor operation for treating ammonia rich digestate lagoon supernatant. Highlights: Anammox activities improved by shortening HRT from 2.5 d to 1.7 d. Anammox activities were inhibited by the high FNA (18.9 ± 8.9 µg L −1 ) at HRT of 1.2 d. Step feeding restored anammox activities. Over 90% of inorganic nitrogen removal was through anammox and the rest through heterotrophic denitrification. AMX nirS gene copy numbers increased by 24.6% in biofilm after changing feeding strategy.